Research Trends in the Field of Special Education in Saudi Scientific Journals: A Bibliometric Analysis - Majed Alsalem; Hana Alzahrani (Umm Al-Qura University, 2022)
This study aims to identify the current status of publishing special education researches in Saudi scientific journals in the period of (2015 - 2021) and provides an analysis of research trends concerning the topics published. The study also sheds light on the variation of topics tackled in the published researches, according to specific criteria which include the research methodology, disabilities categories covered by the studies, samples, academic stages, where studies were geographically conducted, type of participation in publishing, study levels, and research financing. The analysis includes (359) researches from (32) Saudi scientific journals, which are analyzed by using the bibliometric approach. The study arrives at that the percentage of publishing the special education researches has reached (6.97%) of the total studies published in (2015 - 2021). The results indicated the top scientific journals that publishing researches in special education in the targeted period, determining the most studied disability categories, and type of research methods that used in these studies. The findings show the most special education researches have been applied in the main cities in the Kingdom. In terms of the types of authorship, it has been found that researchers are considerably inclined to the individual publication, and only a small number of studies have received financial support. Based on the results of the analysis, recommendations were made to direct scientific research in the field of special education in the future.